The Effect Of Individual Characteristics, Workload, And Work Stress On Employee Performance At The National Land Agency (BPN) Of Bima City - Adyatma Fadhilla; Jaenab, Jaenab; Muhammad Badar (Mellbaou Publisher, 2025)
This study aims to determine the individual characteristics, workload, and work stress that have a significant effect on employee performance at the National Land Agency (BPN) of Bima City. This study is included in the category of associative research, the population in this study were all employees of the National Land Agency (BPN) of Bima City consisting of 20 civil servants (PNS), 10 government employees with work agreements (PPPK) and 19 non-civil servant government employees (PPNPn) with a total of 49 respondents. The sampling method in this study used a purposive sampling technique, with a total sample of 30 respondents. The instrument in this study was a questionnaire with a Likert scale. Data collection techniques were observation, questionnaires, and literature studies. Data analysis techniques used validity tests, reliability tests, classical assumption tests, and multiple linear regressions, then processed using SPSS. The results of the study stated that individual characteristics, workload, and work stress had a significant effect on employee performance at the National Land Agency (BPN) of Bima City